2017
DOI: 10.37358/mp.17.2.4831
|View full text |Cite
|
Sign up to set email alerts
|

Friction and Wear Behaviour of Composite Materials Containing Organic Components

Abstract: The paper presents the experiments performed in the laboratory and the results obtained on friction and wear behaviour of the composite materials for the manufacture of brake shoes used for driving and towed rolling stock. The tribological research of these samples made of composite material with organic components aimed to determine the influence of certain material factors and operating regime parameters on the tribological properties of the tested samples. The brake shoes made of composite materials oneuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…To obtain optimal performance of the composite material, a broad variety of organic and inorganic modification agents are used [3]. The use of agents helps to improve the material by increasing the abrasion resistance and lowering the coefficient of thermal expansion [4]. Few studies, demonstrated the feasibility of using an organic acids as a novel ecofriendly curing agent.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain optimal performance of the composite material, a broad variety of organic and inorganic modification agents are used [3]. The use of agents helps to improve the material by increasing the abrasion resistance and lowering the coefficient of thermal expansion [4]. Few studies, demonstrated the feasibility of using an organic acids as a novel ecofriendly curing agent.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid pace of industrial development has led the specialists, in the technical fields of research and production, to create new materials (composites, ceramic powders, amorphous and nanocrystalline alloys, etc.). If ceramic composite and powder materials are old application [1][2][3][4][5][6][7][8][9], bulk amorphous and nanocrystalline alloys begin to outperform them, in terms of research and practical application, due to their unique physico-chemical and mechanical properties. The researchers have focused mainly on the discovery of new types of metallic glasses with excellent glass forming ability (GFA) so as to allow the production of bulk materials at low cooling rate by conventional casting methods.…”
mentioning
confidence: 99%
“…Keywords: brake pad, composite, organic materials, coconut fiber Current road safety requirements call for the development of new technical solutions for the main components of the vehicle. Their technical performances depend on the physical and mechanical characteristics of the materials which they are made [1,2]. Traditional materials used in automotive design have been studied over the time, so today is know their characteristics, their advantages and disadvantages.…”
mentioning
confidence: 99%
“…Different papers have been reported in the scientific literature on the use of organic fibers in the production of composite materials, such as: pineapple, sisal, coconut shell, jute, palm, cotton, rice husks, bamboo, wood [2,[9][10][11][12][13][14]. Composite materials with coconut fiber have a wide range of applicability in countries such as Malaysia, Indonesia, Thailand, Sri Lanka.…”
mentioning
confidence: 99%
See 1 more Smart Citation